2013
DOI: 10.1179/1743290113y.0000000080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition and milling time on mechanical and wear performance of copper–graphite composites processed by powder metallurgy route

Abstract: Copper–graphite (Cu–Gr) composites with 0, 5, 10 and 15 vol.-% graphite were processed via powder metallurgy route. The effect of composition and milling time on mechanical properties and wear resistance were studied. With increase in vol.-% of graphite, there was decrease in hardness of the composites. However, increasing milling time showed significant increase in hardness of the composites. Compressive strength of the composites containing 5 and 10 vol.-% of graphite was found to be 515 and 393 MPa respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
5
8
0
1
Order By: Relevance
“…The appearance of porosity is in agreement with the results acquired in previous studies [38][39][40]. This behavior will affect the denser character of composites which is confirmed by the decrease of the sintered density As graphite content was increased to 10 wt% of Graphite ( figure 7(c)), the porosity will have a relevant number.…”
Section: Microstructure Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…The appearance of porosity is in agreement with the results acquired in previous studies [38][39][40]. This behavior will affect the denser character of composites which is confirmed by the decrease of the sintered density As graphite content was increased to 10 wt% of Graphite ( figure 7(c)), the porosity will have a relevant number.…”
Section: Microstructure Analysissupporting
confidence: 90%
“…This can be attributed to the lower density of graphite compared to the 2017 Aluminium alloy. Furthermore, the addition of graphite particles reduce the contact area between 2017 Aluminium alloy particles which provides a poor network and a reduction of the sintered density agreeing with many researches [4,[38][39][40]. Also, by exploring the measured densities of composites as function of graphite content for different sintering time and temperature conditions and according to the equation (2), the porosity of composites is calculated and plotted in figure 5(b).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, copper-graphite composites constitute an attractive material for many applications, such as electrical brushes, bearings, and especially tribological engineering parts [1][2][3]. Several techniques have been used to produce copper-graphite composites, such as conventional powder metallurgy, microwave sintering, friction stir processing, and field-assisted sintering [4][5][6][7][8][9]. Generally, studies have shown that copper-graphite composites with finer particle sizes and better distribution exhibit higher load withstanding capacity and lower friction coefficient and wear rate due to a thick graphite layer that forms at the contact surface [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Then, a more continuous graphite layer which reduces the wear debris size is produced. D. Nayak and M. Debata [7] fabricated copper-graphite composites by the powder metallurgy route to study the effect of composition and milling time on the mechanical properties and wear resistance. They found that increasing the milling time yielded a better distribution and finer particle size, which led to a lower wear loss.…”
Section: Introductionmentioning
confidence: 99%